Space Weather The Physics Behind a Slogan - Scherer, Klaus; Fichtner, Horst; Heber, Bernd; Mall, Urs.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
The various processes that connect the physics of the Sun with that of the Earth`s environment has become known as "Space Weather" during recent years, a slogan that has emerged in connection with many other expressions adapted from meteorology, such as solar wind, magnetic clouds or polar rain. This volume is intended as a first graduate-level textbook-style account on the physics of these solar-terrestrial relations and their impact on our natural and technological environment.
Introduction to Space Weather -- The Sun and its Restless Magnetic Field -- The Application of Radio Diagnostics to the Study of the Solar Drivers of Space Weather -- Interplanetary Disturbances -- The Magnetosphere -- Space Weather Effects in the Upper Atmosphere: Low and Middle Latitudes -- Space Weather Effects in the Upper Atmosphere: High Latitudes -- Space Weather Effects on Technology -- Radiation Risks From Space -- Index.
Keywords: Physics; Geophysics; Space sciences; Physics; Extraterrestrial Physics, Space Sciences; Geophysics/Geodesy.; Electronic books